Criminality and penal policy - Đuričić Svetlana (Glasnik Advokatske komore Vojvodine, 2017)
In combating and preventing criminality in general, one of the segments is a penal policy. However, prescribing the strict penalties by increasing a special minimum and maximum will not reduce criminality. In particular, it will not be achieved by prescribing the prohibition of mitigation on imprisonment sentence for the most serious crimes. Namely, the causes of criminality need to be treated, such as: economic, social, political, population migration, unemployment and others. Etiology deals with this as a branch of criminology. The criminality is a 'disease of society' and to treat the disease, its causes need to be considered. This work is an attempt to draw attention to the essence of the problem because it is often considered 'populistically' as an increase of criminality and 'lenient sentences' imposed by the courts, which is contrary to doctrinaire principles and jurisprudence.